Monetary policy, credit constraints and SME employment - Julien Champagne; Émilien Gouin-Bonenfant (Bank of Canada, 2022)
Do financial constraints amplify or dampen the transmission of monetary policy to the real economy? To answer this question, we propose a simple empirical strategy that combines (i) firm-level employment and balance sheet data, (ii) identified monetary policy shocks and (iii) survey data on financing activities. The key novelty of our approach is a new proxy for the likelihood of being credit constrained, which is constructed using survey data on realized outcomes of financing requests. Leveraging cross-sectional heterogeneity in the proxy and the sensitivity of employment to monetary policy shocks, we find that credit constraints amplify the transmission of monetary policy. In the aggregate, credit constraints account for roughly a third of the employment response. Our findings are consistent with a strong financial accelerator, whereby accommodative monetary policy has the indirect effect of improving the ability of firms to obtain credit.
Keywords: E2; E3; E43; E52; G3; 330; Credit and credit aggregates; Econometric and statistical methods; Firm dynamics; Labour markets; Monetary policy